Common Mistakes in Translating Indonesia-English - Balqis, Nabilah; Rahwani, Sintiya; Matondang, Nia Ajmaini; Lubis, Yani (CV. PUSDIKRA MITRA JAYA, 2025)
This study systematically investigates common mistakes in Indonesia-English translation, identifying specific linguistic and cultural pitfalls that compromise target text quality. Utilizing a qualitative, corpus-based approach, the research analyzes a diverse range of translated materials, including academic papers, journalistic articles, and official documents, to pinpoint recurring error patterns. The analysis focuses on four key areas: grammatical inaccuracies (subject-verb agreement, tense usage, article omission), lexical misinterpretations (semantic incongruity, false cognates, collocations), syntactic interference from the source language, and cultural misunderstandings leading to inappropriate pragmatic choices or mistranslation of idiomatic expressions. Findings reveal that while some errors stem from a direct, word-for-word translation approach, others are indicative of a deeper lack of target language competence and cross-cultural awareness. The prevalence of these errors highlights a critical gap in current translation practices, often resulting in texts that are not only grammatically flawed but also unnatural-sounding and potentially misleading to English native speakers. This paper argues that merely possessing bilingualism is insufficient for effective translation; rather, a profound understanding of both the source and target linguistic systems, coupled with a strong grasp of their respective cultural contexts, is imperative. The study concludes by offering pedagogical implications for translator training programs and proposes practical strategies to enhance translation quality, advocating for a more nuanced and context-sensitive approach to Indonesia-English translation.